Nutritional Opportunity and Brain Development among Fetus and Infant - Setyo Handryastuti; Ni Ketut Susila Dharma Asih (World Nutrition Journal, 2022)
The right for optimal cognitive, social, and emotional behavioral growth is fundamental for every child. The cognitive, social, and emotional parts of the brain continue to develop across the lifespan. An immense portion of the brain’s structure and capacity is shaped early in life. Nevertheless, a cautious approach must be undertaken to ensure optimal development with long-term consequences during this sensitive period. Among the identified factors for optimal brain development, provision of optimal nutrition shared its portion as one of the fundamentals. This article will review the essential features of nutrients in the fetal, postnatal, and infancy period in relation to brain development.